(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
Benzothiazole and its derivatives indeed have a rich presence in natural products and pharmaceuticals. They’re fascinating due to their diverse biological activities and structural versatility. These compounds exhibit various pharmacological characteristics and structural diversity, making them a focal point in the advancement of new therapeutic agents. Present study aims to consolidate current information on the pharmacological activities of benzothiazole derivatives, emphasizing their therapeutic potential and underlying mechanisms of action. Benzothiazole derivatives are known for their broad range of biological activities: providing insights into how modifications in their chemical structure can enhance their pharmacological efficacy and selectivity. Given the broad pharmacological profile and therapeutic potential of benzothiazole derivatives, ongoing research and development are likely to yield new and effective drugs for various medical conditions. This review underscores the importance of benzothiazole as a scaffold in drug discovery and encourages further investigation into its diverse pharmacological applications.